Sistem Penerangan Tanaman Sayuran Hidroponik Menggunakan Energi Surya Pada Kelompak Tani dRangrang - setiyono setiyono; Budiman; Sandy Suryo Prayogo; Dhatu Paragya (Universitas Serang Raya, 2024)
The need for lighting to monitor the development of hydroponic vegetable crops at night in the Drangrang farmer group has so far used an electricity source from the Perusahaan Listrik Negara (PLN). Thus, it requires costs to pay for electricity usage every month. This is felt to be quite a burden for farmers because profits are reduced due to additional expenses. The aim of this community service activity is to build a lighting system for pak choy vegetable plants using solar energy for the drangrang farmer group, residents of RT10/RW03, Tirtajaya sub-district, Sukmajaya sub-district, Depok. The method used is to create a solar power plant with a capacity of 200 Wp with a load of incandescent lamps for the lighting needs of vegetable plants at night. The result is that the hydroponic vegetable growing area can be illuminated with 6x@50 W lamps, so that monitoring of the plants can be carried out at any time, both day and night.